2016
DOI: 10.2503/hortj.mi-ir06
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Self-recognition in the <i>Prunus</i> S-RNase-based Gametophytic Self-incompatibility System

Abstract: Prunus fruit tree species exhibit S-ribonuclease (S-RNase)-based gametophytic self-incompatibility (GSI). This system is also present in the families Plantaginaceae and Solanaceae and the tribe Maleae of the family Rosaceae. In S-RNase-based GSI, self/nonself-recognition between the pistil and pollen is controlled by the pistil S determinant S-ribonuclease gene (S-RNase) and the pollen S determinant F-box gene(s). Accumulated evidence indicates the Prunus pollen S locus contains a single F-box gene, while that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 175 publications
2
32
0
Order By: Relevance
“…Additionally, the DeepLoc program predicted that all the proteins are likely to be soluble and localized in the extracellular space (Table 4). This is also a common feature of S-RNases (Anderson et al, 1989;Certal et al, 1999) and is thought to be associated with the nature of the interaction between S-RNase and pollen (Matsumoto and Tao, 2016), suggesting that CtRNS genes are correlated with SI in Citrus.…”
Section: Characterization Of Ctrns1 To Ctrns3 Sequencesmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, the DeepLoc program predicted that all the proteins are likely to be soluble and localized in the extracellular space (Table 4). This is also a common feature of S-RNases (Anderson et al, 1989;Certal et al, 1999) and is thought to be associated with the nature of the interaction between S-RNase and pollen (Matsumoto and Tao, 2016), suggesting that CtRNS genes are correlated with SI in Citrus.…”
Section: Characterization Of Ctrns1 To Ctrns3 Sequencesmentioning
confidence: 91%
“…However, the key genes that determine S haplotypes and function in self/non-self recognition have not yet been identified. Among GSI plant species, the Rosaceae, Solanaceae, and Plantaginaceae families share the same SI system and the molecular mechanisms regulating this process have been better characterized (Matsumoto and Tao, 2016;Tao and Iezzoni, 2010). The SI system in these families is ruled by two different closely linked genes that define the pistil and pollen S specificities.…”
Section: Introductionmentioning
confidence: 99%
“…A number of details remain murky, as these models are highly preliminary and, for example, a general inhibitor necessary for coherence of the proposed self-recognition Prunus model remains unidentified. Nevertheless, these differences appear fairly profound, because we lack a sound theory to explain how minor background mutations could switch between a mechanism with non-self-recognition that inhibits S-RNase cytotoxicity to one in which self-recognition elicits S-RNase cytotoxicity, for each of several dozen segregating alleles ( Matsumoto & Tao, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…5), in which GSI exhibited a distinct system of recognition between pollen and pistil involving a single SFB gene. This contrasts with multiple F-box genes that are activated in other plants (Matsumoto and Tao 2016). With the formerly identified S-RNase gene in Z. jujuba, therefore, we concluded that Jujube GSI behaviour was like Prunus and controlled by the S-RNase and a single SFB gene together.…”
Section: Discussionmentioning
confidence: 62%